RANCANG SIMULASI AUTOMATIC TRANSFER SWITCH (ATS) GENSET BERBASIS OUTSEAL PLC: Rancang Simulasi Automatic Transfer Switch (ATS) Genset Berbasis Outseal PLC - firman al barqah; Paris Ali Topan; Masyitah Aulia (Jurnal Altron, 2023)
Planning Out seal PLC Based Generator Automatic Transfer Switch (ATS) Simulation. This thesis raises the problem that when there is a sudden power outage due to cut off of supply from the PLN, by automatically activating the generator so that it does not take longer in the transition process between the PLN supply and the generator supply. The purpose of this research is to make an ATS tool using a PLC and analyze the results of the ATS test. This research used the R&D (Research and Development) method and was conducted in the electrical engineering laboratory, Faculty of Systems Engineering, Sumbawa University of Technology. The results of the ATS simulation research that has been made are that the tool that has been designed can run according to the design and can work properly, so that in the PLN OFF condition, R5 starts the generator immediately, giving a signal and making the generator program turn on.